Good practices and opportunities for improving the socio-educational accompaniment of young people in protection during the transition to adult life - Fernández Simo, Deibe; Carrera-Fernández, María Victoria; Cid-Fernández, Xosé Manuel; Correia-Campos, Edgar (Revista Complutense de Educación, 2023)
Introduction: Youth in protection are emancipated in a context of vulnerability and lack of social support. The socio-educational accompaniment carried out by professional teams is decisive in facilitating relationships and safety spaces. The educational intervention facilitates the achievement of the goals of the transition to adult life. Goals: 1) Analyze socio-educational accompaniment good practices that allow to configure a safe educational place from which adolescents in protection can face the process of transition to adult life. 2) Define lines of improvement in the protection system that facilitate effective strategies consolidation and overcome existing obstacles. Methodology: It is designed a qualitative research organized in three phases according to the grounded theory, through participant observation of cases (N = 6), longitudinal follow-ups (N = 11) and interviews with professionals (N = 7). The youth sample is made up of eleven men and seven women. Seven social educators participate. In phase one notes are taken in a research reporting notebook and in phases two and three a total of 62 interviews are carried out. Results: The results indicate that the practices of the educational teams have provided professional reference spaces that favor a safe setting from which young people can face the strenuous challenges of adult life. There are bureaucratic and organizational conditions of the protection system that hinder the generalization of effective interventions. It is focused the importance of prioritizing accompaniment times in specific places marked by the daily routine. Conclusions: It is concluded that foster care homes should adapt the work’s organization to the socio-educational perspective of professional teams.
Keywords: child welfare; educational strategies; transition to adult life; protection system